ANALISIS PENINGKATAN USAHA PEDAGANG KULINER DI KAWASAN WISATA PANTAI BUMBUL DESA LUMASEBU KECAMATAN KORMOMOLIN KABUPATEN KEPULAUAN TANIMBAR - Simon Larbona; Merryl Pelamonia; Fransisca R Sinay (Jurnal Administrasi Terapan, 2022)
Culinary business located in the beach tourism area of Lumasebu village is an initiative of the community, therefore the capital and management is regulated by the household itself. Culinary businesses will be widely encountered and also in demand by the public because the prices are affordable by all people, from the lower, middle to upper classes. Culinary sellers such as: meatballs, rujak, sarimento, various fried foods and others.. The purpose of this research is to increase the number of merchandise sold, increase sales volume and find out how much culinary traders earn The subject of this study took 5 traders as respondents. The data analysis technique used in this research is descriptive qualitative statistical analysis. The results showed that the number of merchandise sold, the volume of sales and the income earned by the traders had increased in the business of traders in the beach tourism area of Bubul. Keywords: Culinary Merchant Business Improvemen